2020
DOI: 10.1093/neuonc/noaa297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diverse tumor endothelial cell populations in malignant glioma

Abstract: Background Glioblastoma is the most common and aggressive type of primary brain tumor, as most patients succumb to the disease less than two years after diagnosis. Critically, studies demonstrate that glioma recruits surrounding blood vessels, while some work suggests that tumor stem cells themselves directly differentiate into endothelial cells, yet the molecular and cellular dynamics of the endothelium in glioma are poorly characterized. The goal of this study was to establish molecular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…Indeed, TDECs are resistant to anti-VEGF therapies, which even increase their frequency [ 147 ]. Recently, it has been shown that TDECs differ from tumor-associated vessels and compose molecularly distinct populations [ 149 ].…”
Section: Transdifferentiation Of Gscs Into Vascular-like Cellsmentioning
confidence: 99%
“…Indeed, TDECs are resistant to anti-VEGF therapies, which even increase their frequency [ 147 ]. Recently, it has been shown that TDECs differ from tumor-associated vessels and compose molecularly distinct populations [ 149 ].…”
Section: Transdifferentiation Of Gscs Into Vascular-like Cellsmentioning
confidence: 99%
“…An important characteristic of GBM is the abundance of abnormal vascular systems, and this uncontrolled vascular growth plays a crucial role in the occurrence, progression, and invasion of tumor (Carlson et al, 2020). Elucidating and understanding the molecular mechanism of tumor angiogenesis is very important for the targeted therapy of antitumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these angiogenic members are signaling proteins that couple with stimulating or suppressive cell surface receptors exhibited by vascular endothelial cells. In addition, glial vascular endothelial cells may excrete a considerable quantity of factors that accelerate cancer development ( 98 ). Notably, research has shown that circRNAs can regulate the interactions of these secreted factors to induce angiogenesis.…”
Section: Circrnas and Gliomamentioning
confidence: 99%
“…circRNAs may regulate the interactions of pro-angiogenic factors and glioma growth factors to induce angiogenesis. Angiogenesis is the basis of hematogenous metastasis in glioma and new blood vessels have been characterized as essential channels for glioma to transport nutrients ( 97 , 98 ). These circRNA studies may be useful in designing approaches to improving the survival of patients with glioma.…”
Section: Circrnas and Gliomamentioning
confidence: 99%